Short-term high-intensity rehabilitation in radically treated lung cancer: a three-armed randomized controlled trial - Huang, Jian (J Thorac Dis, 2017)
BACKGROUND: The feasibility and practicality of preoperative rehabilitation (PR) programs remains quite controversial in the treatment of lung cancer (LC). This study explored whether a short-term high-intensity rehabilitation program could improve postoperative outcomes compared to those achieved with conventional inspiratory muscle training (IMT). METHODS: A three-armed randomized controlled trial comparing the two training modalities and routine care was conducted in surgical LC patients. Patient groups received one of three treatment regimens: (I) high-intensity pulmonary rehabilitation (PR) that combined IMT with conventional resistance training (CRT) (combined PR group); (II) conventional PR (single IMT group); or (III) routine preoperative preparation (control group). The primary endpoint was a change in the occurrence of post-operative pulmonary complications (PPCs) that occurred within 30 days after surgery, while secondary endpoints included changes in length of hospital stay, quality of life (QoL) scores, 6-min walk distance (6-MWD) and peak expiratory flow (PEF). RESULTS: A total of 90 enrolled patients were randomized into three groups with a computer-based 1:1:1 ratio. The intention-to-treat analysis of the study revealed that, compared with the Control Group, the Combined PR Group had a significant increase in (∆)6-MWD (by 32.67 m, P=0.002), (∆)PEF (by 14.3 L/min, P=0.001), (∆)global scores (by 3.7, P=0.035); and a reduced (∆)average total hospital stay (by 3.2 d, P=0.001) and ∆postoperative stay (by 3.6 d, P=0.001). With regard to PPC rate, the Combined PR Group had a somewhat lower PPC severity (grade II–V) compared to the Control Group. CONCLUSIONS: This hospital-based short-term program of PR combining high-intensity IMT with CRT was significantly superior to the conventional IMT program, indicating that this approach would be a feasible strategy for treating LC patients, especially those waiting operations with surgery-related risk factors.